2003
DOI: 10.1211/0022357021297
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists' perceptions regarding their contribution to improving the public's health: a systematic review of the United Kingdom and international literature 1990–2001

Abstract: Objective To systematically review, summarise and evaluate the published evidence from 1990–2001 relating to pharmacists' attitudes towards and perceptions of their role in improving the public's health. Methods Electronic databases searched were MEDLINE, EMBASE, Cochrane Library and International Pharmaceutical Abstracts. Hand searches were undertaken of a number of relevant journals and conference abstracts. Studies on pharmacy and health education, health promotion, public health, smoking cessation, diet, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 15 publications
4
58
0
Order By: Relevance
“…Furthermore, this short critical review has highlighted very few studies (qualitative or quantitative) that have moved beyond identifying what pharmacists already do routinely (e.g., health promotion, health education, smoking cessation etc.) (see for example Anderson et al 2003). Basic descriptive and evaluative research, exploring how the pharmacy might already contribute to the development of social capital and community development is required, coupled with case studies of good practice in local areas (Ghalamkari and Jenkins 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this short critical review has highlighted very few studies (qualitative or quantitative) that have moved beyond identifying what pharmacists already do routinely (e.g., health promotion, health education, smoking cessation etc.) (see for example Anderson et al 2003). Basic descriptive and evaluative research, exploring how the pharmacy might already contribute to the development of social capital and community development is required, coupled with case studies of good practice in local areas (Ghalamkari and Jenkins 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As Anderson et al (2003) argue in a recent review of pharmacists' views about their contribution to public health, pharmacists still centrally identify themselves as experts in medicines. There remain significant attitudinal and structural barriers to them developing a sustained and publicly acknowledged role in the provision of health promotion and a reactive approach to this still prevails within the profession .…”
Section: Barriers To Developing Social Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] A review of the published evidence from 1990-2001 relating to pharmacists' attitudes and perceptions towards their role in improving public health showed that they were more comfortable with activities related to medicines and needed additional training to extend their range of health-care activities. 13 The findings of this review have important implications for educators and trainers of pharmacists at undergraduate and postgraduate levels. 13 In most developed nations of the world, many pharmacy schools have integrated public health pharmacy courses as one of the core subjects to be taught in their undergraduate curriculums.…”
Section: Introductionmentioning
confidence: 95%
“…13 The findings of this review have important implications for educators and trainers of pharmacists at undergraduate and postgraduate levels. 13 In most developed nations of the world, many pharmacy schools have integrated public health pharmacy courses as one of the core subjects to be taught in their undergraduate curriculums. 14,15 In Malaysia, improving public health is firmly on the national healthcare agenda and the government's health policy offers an unparalleled opportunity for pharmacists to be recognized as part of the public health workforce.…”
Section: Introductionmentioning
confidence: 95%